Virtual Worlds and Immersive Learning in Higher Education - Ayala Pezzutti, Rocío Janett (2020)
Today's society has become a constant swing of changes in every aspect of life; academic, economic, cultural, political, among others. The changes have been generated with the insertion of technology in daily activities, where learning is not exempt from these changes. According to Negroponte (1995), when science meets technology, it produces significant changes in our lives, as well as the way we understand reality. Today the knowledge society is empowered by technology and by the creation of new and diverse ways of interacting as people; the virtual worlds that are a graphic representation of the reality designed in 3D, is one of them. Second Life is one of these virtual worlds, becoming a site of mere entertainment and social life on the web, to be established in an environment that fosters creativity, collaborative work, business vision, the development of technological skills, the development of experiences of learning in 3D environments, among other aspects. Likewise, immersive learning enables interaction in three-dimensional environments. There the activities are carried out within an artificially constructed world which resembles reality, this allows us to build learning through the person's own experiences in interaction with the environment and the experiences among the users of this virtual world. For this reason, the use of the Second World virtual world is proposed as a training tool in immersive learning.